A Note on Revenue Distribution Patterns and Rent-Seeking Incentive - Sadik-Zada, Elkhan Richard; Loewenstein, Wilhelm (International Journal of Energy Economics and Policy, 2018)
This paper presents a simple model of rent-seeking incentive to explain the emergence and dominance of the rapacious rent-seeking policies in a number of oil abundant developing and transition economies. The Hubbertian distribution of the commodity exports over time, the magnitude of these revenues, and the availability of offshore havens for the illicitly appropriated rent explain the shift from productive public policies to rapacious rent-seeking. In addition, we show that the existence of the well-functioning democratic institutions prior to the revenue boom precludes the emergence of rapacious rent-seeking institutions due to prohibitively high costs of rent-seeking. The paper complements the existing literature by delivering a novel theoretical rationale for the predisposition of the oil-rich countries to the resource curse. Keywords: Rent-Seeking, Illicit Appropriation, Hubbert Curve, Point-Source Resources, Institutions, Offshore Havens JEL Classifications: D72, D73, L72, O13